Overexpression of enzymes in glycolysis and energy metabolic pathways to enhance coenzyme Q10 production in Rhodobacter sphaeroides VK-2-3 - Zhang, Long; Li, Yong-li; Hu, Jian-hua; Liu, Zhan-ying (Frontiers in Microbiology, 2022)
We subjected the components of the glycolysis and energy metabolism pathways of Rhodobacter sphaeroides (R. sphaeroides) to metabolic engineering to improve the titer and yield of coenzyme Q10 (CoQ10). Phosphofructokinase (PFK), cyclic adenylate-dependent protein kinase (PKAC), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and adenosine triphosphate hydrolase (KdpC) were overexpressed in R. sphaeroides VK-2-3 (VK-2-3). The strains were labeled R. sphaeroides PFK (RS.PFK), RS.PKAC, RS.PFK–PKAC, RS.KdpC, RS.GAPDH, and RS.KdpC–GAPDH. Results showed that the CoQ10 titers of RS.PFK, RS.PKAC, and RS.PFK–PKAC were 300.96 ± 0.87, 405.94 ± 4.77, and 379.94 ± 0.42 mg/L, respectively. The CoQ10 titers of RS.PFK and VK-2-3 were not significantly different; however, those for RS.PKAC and RS.PFK–PKAC were 13% and 6% higher than that of VK-2-3, respectively. Further, the titers of RS.KdpC, RS.GAPDH, and RS.KdpC–GAPDH were 360.17 ± 0.39, 409.79 ± 0.76, and 359.87 ± 1.14 mg/L, respectively. The titers of RS.KdpC and RS.KdpC–GAPDH were not significantly different from that for VK-2-3, whereas that for RS.GAPDH was 14% higher than that of VK-2-3. Finally, when the cultures of RS.GAPDH and VK-2-3 were scaled up in 5-L fermenters, the CoQ10 titers and RS.GAPDH yields increased by 44.3% and 37.8%, respectively, compared with VK-2-3.To the best of our knowledge, the glycolysis pathway of R. sphaeroides was studied for the first time in this study. We genetically modified the components of the energy metabolism pathway to obtain the strain with high yield of CoQ10 mutant RS.GAPDH. The findings of this study can serve as a basis for future studies involving metabolic engineering of CoQ10-producing strains.